12, 000 Years of Human Predation on Black Turban Snails (Chlorostoma funebralis) on Alta California's Northern Channel Islands. (June 2015) - Erlandson, Jon M.; Ainis, Amira F.; Braje, Todd J.; Jew, Nicholas P.; McVey, Marlene; Rick, Torben C.; Vellanoweth, René L.; Watts, Jack
Abstract : Examining the ecology and archaeology of black turban snails ( Chlorostoma [Tegula] funebralis ), found along North America's Pacific Coast from British Columbia to Baja California, we present evidence for 12, 000 years of human predation in Northern Channel Island shell middens. Often viewed as evidence for Late Holocene economic intensification along the southern California Coast, we identified black turban middens dated to the terminal Pleistocene, as well as the early, middle, and late Holocene. Despite their small size and lower ranking as a prey species, humans harvested black turban snails because of their abundance, aggregation, and accessibility during daily tidal cycles. Examining 19 discrete archaeological components (with a total MNI of ∼7, 800) from San Miguel and Santa Rosa islands, we used a Shell Weight/MNI Index to document fluctuations in the mean size of black turban shells through time, identifying patterns attributed to a combination of environmental and demographic changes, including variation in the intensity of human predation.